2016
DOI: 10.1103/physrevb.94.174435
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lattice dynamics on the phase stability of metamagnetic FeRh: Bulk and thin films

Abstract: We present phonon dispersions, element-resolved vibrational density of states (VDOS) and corresponding thermodynamic properties obtained by a combination of density functional theory (DFT) and nuclear resonant inelastic x-ray scattering (NRIXS) across the metamagnetic transition of B2 FeRh in the bulk material and thin epitaxial films. We see distinct differences in the VDOS of the antiferromagnetic (AF) and ferromagnetic (FM) phases, which provide a microscopic proof of strong spin-phonon coupling in FeRh. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 121 publications
(306 reference statements)
9
59
0
Order By: Relevance
“…Both properties may change at a magnetostructural transition. This is expressed quantitatively in terms of the vibrational density of states (VDOS) g ( ϵ ), which can be measured by inelastic neutron scattering or nuclear resonant inelastic X‐ray scattering . VDOS and phonon dispersion relations have been calculated from first principles achieving excellent agreement with experimental data .…”
Section: Disentangling the Microscopic Contributions To The Entropy Cmentioning
confidence: 89%
See 3 more Smart Citations
“…Both properties may change at a magnetostructural transition. This is expressed quantitatively in terms of the vibrational density of states (VDOS) g ( ϵ ), which can be measured by inelastic neutron scattering or nuclear resonant inelastic X‐ray scattering . VDOS and phonon dispersion relations have been calculated from first principles achieving excellent agreement with experimental data .…”
Section: Disentangling the Microscopic Contributions To The Entropy Cmentioning
confidence: 89%
“…This is expressed quantitatively in terms of the vibrational density of states (VDOS) g ( ϵ ), which can be measured by inelastic neutron scattering or nuclear resonant inelastic X‐ray scattering . VDOS and phonon dispersion relations have been calculated from first principles achieving excellent agreement with experimental data . The expression for S lat resembles S el , where the expression in the parentheses takes into account the Bosonic character of the phonons through the Bose–Einstein distribution function n ( ϵ , T )=(exp( ϵ / k B T )−1) −1 for the occupation numbers, which becomes large for high T or small phonon energies ϵ : trueSnormallnormalanormalt=31.69998ptkB0g()ϵ[1+n()ϵ,Tln1+n()ϵ,T-nϵ,Tlnn()ϵ,T]1.69998ptnormaldϵ4pt …”
Section: Disentangling the Microscopic Contributions To The Entropy Cmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been shown that a magnetic state change of Rh between antiferromagnetism (with a Rh moment of 0 μ B ) and ferromagnetism (≈0.9 μ B ), accompanied by a significant change in electronic structure, combine as the main origin of the metamagnetic transition . To be more precise, it is the cooperative contribution of electronic, magnetic, and vibrational degrees of freedom that is responsible for the giant magnetocaloric effect in FeRh . The alloy Ni 45 Co 5 Mn 32 Cr 5 In 13 is stable with respect to decomposition into all individual elements.…”
Section: Magnetostructural Phase Transition Of Rapidly Quenched Heuslmentioning
confidence: 99%